A rapid assay to screen adenosine deaminase inhibitors from Ligustri Lucidi Fructus against metabolism of cordycepin utilizing ultra‐high‐performance liquid chromatography–tandem mass spectrometry. (8th January 2020) - Guan, Huida; Qi, Shenglan; Liu, Wei; Ma, Chao; Wang, Changhong
Abstract: Cordycepin has recently received increased attention owing to its extensive pharmacological activity. Adenosine deaminase (ADA) is widely distributed in mammalian blood and tissues; as a result, cordycepin is quickly metabolized upon entering into the body and converted into the inactive metabolite 3′‐deoxyinosine, thus limiting its activity when administered alone. We herein present a novel ultra‐high‐performance liquid chromatography–tandem mass spectrometry (UHPLC–MS/MS) method for screening ADA inhibitors against the metabolism of cordycepin. Cordycepin and 3′‐deoxyinosine were chosen as substrate and product, respectively. A proper separation was achieved for all analytes within 3 min. 3′‐Deoxyinosine was quantified in the presence or absence of potential ADA inhibitors to evaluate ADA activity. The assay can simultaneously determine substrate and product, with the endogenous substance and ADA inhibitors added not interfering in its activity. After optimizing the enzymatic incubation and UHPLC–MS/MS conditions, Km and Vmax values for ADA deamination of cordycepin were 95.18 ± 7.85 μm and 363.90 ± 12.16 μmol/min/unit, respectively. Oleanolic acid and ursolic acid from Ligustri Lucidi Fructus were chosen as ADA inhibitors with half maximal inhibitory concentration values of 21.82 ± 0.39 and 18.41 ± 0.14 μm, respectively. A non‐competitive inhibition model was constructed and this assay can be used to screen other potential ADA inhibitors quickly and accurately.